2001
DOI: 10.1097/00001756-200107030-00018
|View full text |Cite
|
Sign up to set email alerts
|

Error-related brain potentials elicited by vocal errors

Abstract: Error-related negativity (ERN) is observed immediately after an error in choice reaction time tasks performed by hand response. We examined whether the ERN occurs in relation to slips of vocalization in the Stroop color word task. In one condition, the subject's vocal responses were masked by continuous pink noise in order to prevent vocalization-related cortical potentials from contaminating the ERN time window. This masking procedure was successful in inhibiting the vocalization-related cortical potential. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 16 publications
4
63
0
3
Order By: Relevance
“…The results emphasize that the brain has a general-purpose control system that can be applied to monitoring outcomes of behavior across many domains. Cognitive neuroscience research has already demonstrated ERN and FRN responses to errors and losses in many contexts-errors committed with hands and feet (Holroyd, Dien, & Coles, 1998), errors in buttonpressing and errors in speech (e.g., Masaki, Tanaka, Takasawa, & Yamazaki, 2001), or errors of commission and errors of timing (e.g., Luu, Flaisch, & Tucker, 2000;Miltner et al, 1997). The anterior cingulate cortex is also activated by cognitive dissonance (van Veen, Krug, Schooler, & Carter, 2009), implying that conflict between internal attitudes and behavior can produce an error-like neural response.…”
Section: Discussionmentioning
confidence: 99%
“…The results emphasize that the brain has a general-purpose control system that can be applied to monitoring outcomes of behavior across many domains. Cognitive neuroscience research has already demonstrated ERN and FRN responses to errors and losses in many contexts-errors committed with hands and feet (Holroyd, Dien, & Coles, 1998), errors in buttonpressing and errors in speech (e.g., Masaki, Tanaka, Takasawa, & Yamazaki, 2001), or errors of commission and errors of timing (e.g., Luu, Flaisch, & Tucker, 2000;Miltner et al, 1997). The anterior cingulate cortex is also activated by cognitive dissonance (van Veen, Krug, Schooler, & Carter, 2009), implying that conflict between internal attitudes and behavior can produce an error-like neural response.…”
Section: Discussionmentioning
confidence: 99%
“…However, unlike the ERN, an auditory-evoked potential is independent of response correctness. Masaki et al (2001) used loud pink noise to suppress the vocalization-elicited components. In the current study, we did not use any masking procedure.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, however, we use the ERN to explore the workings of the verbal monitoring system. There are only few studies that looked at the ERN after verbal errors (see Ganushchak and Schiller, 2006, in press;Masaki et al, 2001;Möller et al, 2007;Sebastián-Gallés et al, 2006), which we will briefly review below.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that the ERN is indifferent to modality of the error information (Holroyd and Coles, 2002), it seems plausible to assume that the ERN will also be generated by verbal errors. One study conducted by Masaki et al (2001) examined whether the ERN occurs in relation to speech errors in the Stroop color-word task. Participants were instructed to overtly name the color of each stimulus as quickly and accurately as possible.…”
Section: Current Studymentioning
confidence: 99%